HUBUNGAN TINGKAT KONSUMSI ENERGI DENGAN PRODUKTIVITAS KERJA PEKERJA SORTASI LANSIA DI KEBUN KLAMBIR V PTPN II TAHUN 2012 - Nona Nova Harianti; Kalsum .; Eka Lestari Mahyuni (Lingkungan dan Kesehatan Kerja, 2012)
Correlation Between Energy Consumption and Productivity of Workers Are Elderly Sorting Workers at Klambir V PTPN II 2012. Level of energy consumption is take from food consumption, every worker have relation with productivity when do work. This research is quantitative design analytical survey to analyze the relation between level of energy consumption and productivity of elderly sorting workers at the Kebun Klambir V PTPN II in 2012. Samples based on purposive sampling as many as 25 people from contract workers at Kebun Klambir V PTPN II.The study of energy consumption using food recall questioner the productivity showed with the leaves of tobacco bonds.The result of good level energy consumption 13 people (52,0%), 9 peoples with appropriate productivity (69,2%) and 4 people with unappropriate productivity (30,8%). Less level energy consumption there are 12 people (48,0%) with less energy consumption no one with appropriate productivity and 12 (100%) with unapporpriate productivity. This relation between level of energy consumption and productivity showed signfiicant result which meant there were relation between level of energy consumption and productivity (P=0,000). Key words : level of energy consumption, productivity, elderly sorting worker.